Resveratrol attenuates staphylococcal enterotoxin B-activated immune cell metabolism via upregulation of miR-100 and suppression of mTOR signaling pathway - Alghetaa, Hasan; Mohammed, Amira; Singh, Narendra; Wilson, Kiesha; Cai, Goushuai; Putluri, Nagireddy; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Pharmacology, 2023)
Acute Respiratory Distress Syndrome (ARDS) is triggered by a variety of insults, such as bacterial and viral infections, including SARS-CoV-2, leading to high mortality. In the murine model of ARDS induced by Staphylococcal enterotoxin-B (SEB), our previous studies showed that while SEB triggered 100% mortality, treatment with Resveratrol (RES) completely prevented such mortality by attenuating inflammation in the lungs. In the current study, we investigated the metabolic profile of SEB-activated immune cells in the lungs following treatment with RES. RES-treated mice had higher expression of miR-100 in the lung mononuclear cells (MNCs), which targeted mTOR, leading to its decreased expression. Also, Single-cell RNA-seq(scRNA seq) unveiled the decreased expression of mTOR in a variety of immune cells in the lungs. There was also an increase in glycolytic and mitochondrial respiration in the cells from SEB+VEH group in comparison with SEB+RES group. Together these data suggested that RES alters the metabolic reprogramming of SEB-activated immune cells, through suppression of mTOR activation and its down- and upstream effects on energy metabolism. Also, miR-100 could serve as novel potential therapeutic molecule in the amelioration of ARDS.